Heparan Sulfate as a Therapeutic Target in Tauopathies: Insights From Zebrafish - Alavi Naini, Seyedeh Maryam; Soussi-Yanicostas, Nadia (Frontiers in Cell and Developmental Biology, 2018)
Hyperphosphorylation and aggregation of the microtubule-associated protein tau (MAPT), are two hallmarks of a family of neurodegenerative disorders collectively referred to as tauopathies. In many tauopathies, including Alzheimer’s disease, Pick’s disease and progressive supranuclear palsy, tau aggregates have been found associated with highly sulfated polysaccharide chains known as heparan sulfates (HSs). In addition, in vitro studies have shown that HSs are critical for the binding of extracellular tau aggregates to cell membranes and for their subsequent uptake and internalization, which are key processes in the spreading of tau pathology. Moreover, it has been demonstrated in vitro that heparin, an HS analog, promotes hyperphosphorylation, misfolding and aggregation of the tau protein. Recently, to gain a better understanding of the HS requirements in the pathophysiology of tauopathies in vivo, we have made use of the transgenic Tg[HuC:hTauP301L; DsRed] zebrafish model of tauopathy in which CNS neurons express the tauopathy-causing TauP301L human mutant protein that leads to tau hyperphosphorylation combined with neurological defects, which impair both larval motility and motor neuron axon growth. First, we showed that genetic knockdown of the zebrafish 3-O-sulfotransferase-2 (3ost2) gene, which encodes an enzyme required for proper 3-O-sulfation of HS chains, significantly decreased tau hyperphosphorylation in Tg[HuC:hTauP301L; DsRed] larvae and significantly rescued their motion deficit and motoneuron axon defects. More recently, using the same zebrafish line and synthetic small molecules with HS antagonist activities, we confirmed an essential requirement for HSs in tau pathology and demonstrated that treatment of Tg[HuC:hTauP301L; DsRed] embryos with HS antagonists markedly diminished tau hyperphosphorylation and significantly rescued axon growth defects and motion deficits. In this review, we take a comprehensive look at our current knowledge of the role of HSs in tau pathology and discuss novel insights establishing HS antagonist entities as promising therapeutic agents for the treatment of these diseases.